TINJAUAN YURIDIS PENYALAHGUNAAN WEWENANG OLEH KEPALA KANTOR WILAYAH BADAN PERTANAHAN NASIONAL PROVINSI JAMBI BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG PUTUSAN ADMINISTRASI PEMERINTAHAN (STUDI NOMOR 16/G/2021/PTUN.JBI): Misuse Of Authority Of The Head Of The Bpn Wil Kanwil Jambi Province Under Law No. 30 Year 2014 - Shakia Salsabila Putri; Ferry Edwar (Faculty of Law, Universitas Trisakti, 2025)
This research analyzes Decision Number 16/G/2021/PTUN.JBI regarding alleged abuse of authority by the Head of the Jambi Province BPN Regional Office based on Law Number 30 of 2014 concerning Government Administration. In addition, this research examines the suitability of sanctions imposed with Government Regulation Number 53 of 2010 concerning Civil Servant Discipline. The research problem main aspects: Is the Head of the Jambi Province BPN Regional Office proven to have abused authority in resolving land disputes? And are the sanctions imposed in accordance with applicable regulations? Using normative juridical methods with a descriptive approach, this research analyzes secondary data qualitatively and concludes it deductively. The research results and the conclusion showed that the official was proven to have abused his authority, violating the Government Administration Law. As a result, he was given severe disciplinary sanctions in the form of dishonorable dismissal in accordance with Government Regulation Number 53 of 2010